Glossopharyngeal and vagus neuropathy associated to stylopharyngeus muscle compression in horse guttural pouch – Case report - Alonso, Juliana de Moura [UNESP]; Hussni, Carlos Alberto [UNESP]; Watanabe, Marcos Jun [UNESP]; Alves, Ana Liz Garcia [UNESP]; Marsiglia, Marília Ferrari; Rodrigues, Celso Antônio [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
Neuropathies of pharyngeal branches of glossopharyngeal and vagus are often associated with guttural pouches diseases; however, these branches of injury due to stylopharyngeus muscle compression are not reported. A case was reported of a quarter horse mare, 8 years old, 450 kg, presenting dyspnea and respiratory noise associated with weight loss. Clinical examination observed mixed dyspnea, tachycardia, dysphagia, sialorrhea, lung crackles and submandibular and parotid lymphadenopathy. Endoscopic exam showed right arytenoid chondritis, nasopharyngeal collapse, generalized larynx edema and dorsal displacement of the soft palate. Right guttural pouch evaluation showed swelling in the origin of stylopharyngeus muscle with consequent compression of the XII, X and IX cranial nerves. Tracheotomy, systemic treatment with corticosteroids, beta lactams and aminoglycosides antibiotics were performed. No resolution was observed and, after 16 days, the animal showed clinical worsening, developed pleuropneumonia, uveitis, severe sepsis, acute renal failure and was euthanized. The mixed neuropathy resulted in rapid clinical deterioration of the animal, due to the difficulty in swallowing and consequent associated respiratory processes. This report emphasizes the importance of evaluating stylopharyngeus muscle origin in cases of nasopharyngeal collapse associated with dysphagia in horses, given the possibility that structural changes in this muscle can result in laryngeal neuropathy.
Neuropatia do glossofaringeo e vago associada à compressão pelo musculo estilofaringeo em bolsa gutural de equino – Relato de caso
Keywords: Dysphagia; Dyspnea; Equine; Nasopharyngeal collapse